PENGEMBANGAN KEWIRAUSAHAAN MAHASISWA DAN ALUMNI GUNA ERA DIGITAL - Indah Ambarita; Anton Sihombing; Relita Buaton (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2018)
Technological advances that are always developing have a correlation with human patterns and behavior in general. Internet use is not only used to access information or news, but is also used for business facilities and buying and selling transactions. Conventional marketing or promotion is no longer optimal at this time, so that business people must also be directed to utilize information technology or commonly called commercial electronics as a medium for the promotion and sale of production goods. This opportunity becomes a huge opportunity for students or alumni in information technology or computer science such as STMIK Kaputama students or alumni. SMEs (Small and Medium Enterprises) in various regions have been successful in terms of production, but have problems in terms of marketing and sales. This has the potential to be developed by young entrepreneurs, new and creative by utilizing students and alumni so that they synergize between SMEs and entrepreneurs to handle online marketing and sales, so that market reach and sales are broad and increasing. The solution provided is to involve several stakeholders and several activities namely entrepreneurship training that is in touch with how the existing human resources are improved by providing various life skills and increasing entrepreneurial insight. E-commerce making training, making graphic design training, providing coffee bean processing equipment to instant coffee powder, guidance and supervision. With this dedication activity, it produces every year new, young and creative entrepreneurs based on science and technology that synergize with SMEs and coffee farmers, so that SMEs are greatly helped to market their products with the hope that their entrepreneurs and SMEs will increase their welfare.